Parental Challenges In Caregiving For Children With Cancer - Surendran, Rajaratnam (2013)
The objective of this qualitative study was to explore the experience faced by the caregivers of children with cancer in terms of challenges that the illness brings along and their employed coping strategies. The study was conducted on eight respondents who are primary informal caregivers being purposively selected from Penang Hospital. The selection was based on two criteria, namely a) functional level of the patient and b) ethnic background of the family. The scope of the study includes: a) challenges faced by the caregivers, b) social support received by the caregivers, and c) their coping strategies. Study findings revealed that the caregivers faced similar challenges as those from the literature. However, there are dissimilar opinions from the respondents which were discussed in this study. Among others, the challenges faced by caregivers were not limited to financial, but also involve medical caregiving for their ill child; emotional caregiving for their ill child; and caregiving for the siblings of the ill child. Respondents’ perception towards social support that they received and their coping strategies were also explored to better understand the emotional journey throughout their caregiving trajectory. Findings from this study also points out that adequate social support are vital for the caregivers. Thus, medical social workers have the prospect to reduce the respondents’ negative emotions through relevant interventions.